2015
DOI: 10.1038/ncomms8368
|View full text |Cite
|
Sign up to set email alerts
|

Morphological plasticity of the coral skeleton under CO2-driven seawater acidification

Abstract: Ocean acidification causes corals to calcify at reduced rates, but current understanding of the underlying processes is limited. Here, we conduct a mechanistic study into how seawater acidification alters skeletal growth of the coral Stylophora pistillata. Reductions in colony calcification rates are manifested as increases in skeletal porosity at lower pH, while linear extension of skeletons remains unchanged. Inspection of the microstructure of skeletons and measurements of pH at the site of calcification in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
176
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(199 citation statements)
references
References 45 publications
20
176
3
Order By: Relevance
“…If correct, this hypothesis would suggest that P. lutea has a stronger capacity than M. aequituberculata to alter skeletal porosity in order to maintain linear extension. Stylophora pistillata, for example, exploits this strategy when growing at low pH (7.2), which results in depressed calcification, by increasing skeletal porosity (Tambutté et al 2015). A similar trend has been reported for the temperate coral Balanophyllia europaea (Fantazzini et al 2015).…”
Section: Discussionsupporting
confidence: 51%
“…If correct, this hypothesis would suggest that P. lutea has a stronger capacity than M. aequituberculata to alter skeletal porosity in order to maintain linear extension. Stylophora pistillata, for example, exploits this strategy when growing at low pH (7.2), which results in depressed calcification, by increasing skeletal porosity (Tambutté et al 2015). A similar trend has been reported for the temperate coral Balanophyllia europaea (Fantazzini et al 2015).…”
Section: Discussionsupporting
confidence: 51%
“…A change in morphology during incubation at elevated pCO 2 conditions was also observed for the tropical scleractinian coral species S. pistillata (Tambutte et al, 2015). Tambutte and colleagues found that these morphological alterations were accompanied by an increased incorporation of organic matrix proteins into the skeleton, which was suggested to occur to facilitate calcification at lower aragonite saturation by catalysing the precipitation of new aragonite crystals (Mass et al, 2013).…”
Section: Morphological Alterationsmentioning
confidence: 73%
“…Since coral calyces have complex 3-D shape such that their skeletal surface area is actually much greater than the planar area of the colony surface (Barnes, 1970), this implies that calcifying surface area is an important factor in determining coral calcification rates and it complicates the use of bulk calcification rates for estimating Ar (Raybaud et al, 2017). Multiple studies using micro-CT have shown increases in porosity and surface-area : volume ratios in corals cultured under elevated CO 2 levels (Tambutté et al, 2015;Foster et al, 2016). This may represent a strategy for controlling calcifying surface area (i.e.…”
Section: Discussionmentioning
confidence: 99%